KAJIAN POTENSI PENINGGALAN ARKEOLOGI CANDI BARONG SEBAGAI SUMBER BELAJAR SEJARAH - Naufal Raffi Arrazaq (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2026)
Archaeological heritage holds significant potential as a contextual learning resource in history education; however, its utilization within formal educational settings remains suboptimal. This article aims to analyze the potential of Candi Barong as a source of historical learning at the senior high school (SMA) level. The study employs a qualitative research method. The findings indicate that Candi Barong possesses multidimensional educational values derived from its historical background, religious symbolism, architectural characteristics, and cultural landscape, all of which are relevant to the senior high school history curriculum. The site can be effectively integrated into history learning through site-based experiential activities, the development of visual and digital learning media, and the preparation of instructional materials grounded in local history. Furthermore, its utilization supports the development of students’ historical thinking skills, enhances contextual understanding, and fosters awareness of cultural heritage preservation. Therefore, Candi Barong represents a strategic and innovative historical learning resource capable of improving the quality of history education while simultaneously strengthening efforts to preserve archaeological heritage through an educational approach.